Instagram's Impact on Rural Colombian English Education: A Fourth Industrial Revolution Perspective - Méndez, Nikolai Castro (MO.RI Publishing, 2024)
In the Fourth Industrial Revolution, characterized by rapid technological advancements, traditional educational models must evolve. This study examines the potential of Instagram, a widely-used social media platform, as a tool for English language education in rural Colombia. With over a billion active users, Instagram offers unique opportunities for immersive language learning. By integrating Instagram, educators can create dynamic, interactive learning environments for students in areas with limited access to traditional resources. This approach addresses digital age challenges and promotes inclusivity and accessibility in education. Through literature analysis, case studies, and firsthand experiences, the study highlights Instagram's transformative role in language education. It examines Instagram's impact on learning outcomes, student engagement, and teaching practices, providing valuable insights for educators aiming to leverage social media for educational purposes in diverse contexts.